Avaliação das ações do Núcleo de Apoio à Saúde da Família (NASF) em Macaíba/RN - Nóbrega, Jane Suely de Melo (2013)
This research evaluated the contribution of the Support Center for Family Health (SCFH) in relation to its effect on the Family Health Units through perception of the Family Health Strategy (FHS) and SCFH professionals, in addition to the satisfaction of users in relation to that role. Data were collected in the public health services of the city of Macaíba-RN in 2012, through semi-structured questionnaire and non participant systematic observation and it counted as investigated subjects 272 individuals (60 FHS professionals, 12 SCFH professionals and 200 users representatives of 20 units). For analysis of the responses of the opened questions was used categorization process and, in relation to the observational method, that was based on checking the space organization, the characteristics of the participating subjects and the specific set of activities performed by SCFH teams through an observation guide. The results point to a good acceptance of the SCFH teams role by most FHS professionals who reported active participation in the health units routine, its integration activities to the FHS teams with resolving based health promotion actions. Regarding the SCFH professionals, they also reported positive contribution by participating actively in the units routine with integrated activities to the ESF teams and developing resolute actions. For users, the SCFH brought assurance services with better access to specialized, resolving and welcoming care. Systematic observation ratified data obtained by questionnaire. It was perceived the need to implement actions related to man`s health, to invest in expanding the number of the SCFH teams, the greater supply of medications, improving the regulatory process and planning together as a key strategy to promote a more effective integration between teams SCFH / FHS